A usability study of online library systems: A case of Sultanah Bahiyah Library, Universiti Utara Malaysia - Bohari, Abdul Manaf; Amer, Shukry Aboulgasem; Fuad, Nurwahida (2010)
The purpose of this study was to investigate usability of online library systems in Universiti Utara Malaysia (UUM). This study evaluated the usability of Sultanah Bahiyah Library’s web based systems by investigating the aspects of simplicity, comfort, user friendliness, control, readability, information adequacy/task match, navigability, recognition, access time, relevancy, consistency and visual presentation. This study examined user’s views about the usability of digital libraries whereas current and perceived importance. A sample of 45 students of Master of Business Administration (MBA) has been chosen. The Sultanah Bahiyah Library’s web based systems is very important especially for students and academic staffs of Universiti Utara Malaysia. The usability of the Library’s web based systems makes students easy to connect and for that the website should be helpful and attractive within good contents. The result found that the parallel nature of the users’ current views about the usability of digital libraries and users’ perceived importance of digital library usability allows direct comparison of all usability properties. The overall results yielded significant difference for the variables of user’s current views and perceived importance.